(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2013)
Malaysia is expected to be an ageing nation by the year 2030. Life expectancy will have increased, making it important for the aged to be financially independent after retirement. This article seeks to address this issue by analysing the existing legal framework on retirement. This article also illustrates the efforts taken by the government in preparation for the increase in the number of senior citizens. However, it is felt that more is needed to be done in order to ensure the senior citizens are financially independent after retirement. Planning for retirement must start as early as possible. Keywords: retirement, retiree, senior citizens, life expectancy, finance, planning